Being Away from Purun: Women’s Experiences in Peatland Area of Hulu Sungai Utara, South Kalimantan - Enik Maslahah (Jurnal Perempuan, 2020)
Purun is a typical plant that grow in peatland area that has important functions for people living in peatland area. The availability of purun is now decreasing due to changes in land management and environmental destruction. Almost all of the plantation commodities in the peatlands area, management of peatlands in the forestry, agriculture, plantation and fisheries sectors apply exploitative and pragmatic methods, while ignoring environmental sustainability. Furthermore, environmental damage also occurs due to disasters such as forest and land fires that often occur in peatland areas in Indonesia. One of the damages happen to peatland area is the damage and scarcity of purun. As users and beneficiaries of purun, women become the affected group that face  the impact of peatland destruction. This paper describes the experiences and efforts of women in peatland areas to restore land and restore the existence of purun in their villages.